Effect of Vitamin D Supplementation on In Vitro Fertilization Outcomes: A Trial Sequential Meta-Analysis of 5 Randomized Controlled Trials - Zhou, Xiaoting; Wu, Xiaomei; Luo, Xi; Shao, Jingyi; Guo, Dongqun; Deng, Bo; Wu, Ze (Frontiers in Endocrinology, 2022)
Despite numerous studies indicating an imperative role of vitamin D for reproduction, the importance of vitamin D supplementation on in vitro fertilization (IVF) outcomes remains controversial. We therefore performed this meta-analysis to investigate the IVF outcomes of vitamin D supplementation in infertile women with vitamin D deficiency. We systematically searched PubMed, Embase and the Cochrane library for identifying all relevant studies published before August 2021. Pregnancy rate was defined as the primary outcome while good quality embryo, fertilization rate, ongoing pregnancy and miscarriage were secondary outcomes. We used Review Manager 5.3 (RevMan) to conduct meta-analysis and examined the robustness of the primary outcome by trial sequential analysis. Five studies were included in the final analysis and it suggested that vitamin D supplementation was associated with improved chemical pregnancy rate (risk ratio [RR] =1.53, 95% confidence interval [CI] =1.06 to 2.20, p=0.02) but not benefited in improving clinical pregnancy rate (RR=1.34, 95% CI=0.81 to 2.24, p=0.25) and all secondary outcomes. Trial sequential analysis suggested further studies are needed to confirm this conclusion. We concluded that vitamin D supplementation should be prescribed to improve chemical pregnancy in infertile women with vitamin D deficiency and more studies are required to further confirm this finding.